2022
DOI: 10.1093/ehjdh/ztac059
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record-based facilitation of familial hypercholesterolaemia detection sensitivity of different algorithms in genetically confirmed patients

Abstract: Familial hypercholesterolaemia (FH) is a disorder of LDL-cholesterol clearance, resulting in increased risk of cardiovascular disease. Recently, we developed a Dutch Lipid Clinic Network (DLCN) criteria-based algorithm to facilitate FH detection in electronic health records (EHR). In this study, we investigated the sensitivity of this and other algorithms in a genetically confirmed FH population. All patients with a healthcare insurance-related coded diagnosis of ‘primary dyslipidaemia’ between 2018-2020 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In line with all of the above mentioned findings are the results of several studies, showing significant variability in the accuracy of clinical algorithms in those with genetically confirmed FH [ 33 , 34 ]. One extreme example represents the analysis by Mohammadnia et al .…”
Section: Genetic and Phenotypic Heterogeneity Of Fhsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with all of the above mentioned findings are the results of several studies, showing significant variability in the accuracy of clinical algorithms in those with genetically confirmed FH [ 33 , 34 ]. One extreme example represents the analysis by Mohammadnia et al .…”
Section: Genetic and Phenotypic Heterogeneity Of Fhsupporting
confidence: 83%
“…One extreme example represents the analysis by Mohammadnia et al . [ 33 ], who demonstrated that the sensitivity of currently available scores for the clinical FH diagnosis in subjects, positive for FH gene mutations is only modest, being 9% for DLCN 6, 17% for SB and 31% for MEDPED. Within another clinical cohort, analyzing genomic sequence and clinical data from 50,726 individuals from the Geisinger Health System, showed that only 24% out of 215 carriers of a FH variant met criteria for definite or probable clinical FH.…”
Section: Genetic and Phenotypic Heterogeneity Of Fhmentioning
confidence: 99%